Biocontrol of rice blast by Pseudomonas mosselii PR5 through seed priming and foliar application reduces reliance on chemical pesticides - Razia Sultana; Prinon Saha; Shah Mohammad Naimul Islam; Mohammad Mahbubul Haque; Sourav Biswas Shuvo; Md. Mustafijur Rahman Khan; Seikh Jafor Ahmed (PLoS ONE, 2026)
Rice blast caused by Magnaporthe oryzae is a destructive disease that can infect rice at any developmental stage. This study investigated the biocontrol potential of the endophytic bacterium Pseudomonas mosselii PR5 against rice blast in comparison with a chemical fungicide. Three blast-susceptible rice genotypes were evaluated under eight treatment combinations, including an absolute control, a pathogen-inoculated control, a fungicide control, and five PR5 application modes: seed priming (SP), seedling priming (SeP), bacterial culture filtrate (BCF) foliar spray, and the combinations SP + BCF and SeP + BCF. All treatments except the absolute control received pathogen inoculation. Both PR5 and the fungicide significantly reduced disease severity across the three genotypes. The pathogen-only treatment consistently recorded the highest percent disease index (PDI) and area under the disease progress curve (AUPDC). Among the bacterial treatments, SP + BCF produced the lowest AUPDC in V1 and V3, while the fungicide performed best in V2. PR5 inoculation also enhanced plant growth and yield. Shoot dry weight increased by 3.29–47.36% compared with the absolute control and by 10.10–107.43% compared with the pathogen-only treatment. Pathogen stress severely reduced root growth, whereas PR5, particularly in the SeP + BCF treatment, increased root biomass by 24.58–69.22%. Significant improvements in yield traits like grains per panicle, effective tillers, and reduced chaffy grains were observed, especially when priming was combined with BCF foliar application. SP + BCF achieved the highest yield and outperformed the fungicide in disease suppression. These results suggest that PR5-based seed or seedling priming combined with BCF foliar application is a promising strategy for sustainable rice blast management.